Characterization of MEMS Coriolis Vibratory Gyroscopes - Madeira, Bernardo Pereira (2021)
A MEMS Gyroscope is a micromachined inertial sensor that can measure the angle of orientation or the angular rate of rotation. These devices have the potential to be used in high precision navigation, safety and consumer electronics applications. Due to their complexity, MEMS Gyroscopes are prone to have imperfections that inhibit their full potential. By deeply characterizing these sensors, it is possible to validate fabrication methodologies, apply control circuit mechanisms, and design alternative mechanical structures that improve the performance. In this project, a streamlined methodology for testing and characterizing these devices is presented and executed. Analysis to the obtained results is given. Aditionally, a prototype circuit was designed to operate the sensors in a closed-loop mode. Two families of gyroscopes with different thickness were characterized - 40 m and 100 m. The devices presented low sensitivity thresholds due to the presence of a large quadrature error. A phase sensitive demodulation solution was provided to eliminate this noise source. The 40 m presented an overall better performance. A Python Script to extract key noise performance parameters was also displayed.